2015
DOI: 10.1213/xaa.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Superior Laryngeal Nerve Block During Awake Fiberoptic Intubation

Abstract: We report 5 patients who underwent ultrasound-guided superior laryngeal nerve block before awake intubation and general anesthesia. We used a 8- to 15-MHz hockey stick-shaped ultrasound transducer (HST15-8/20 linear probe, Ultrasonix) to visualize the superior laryngeal nerve. A 3.8-cm 25-G needle was inserted in real time and directed toward the superior laryngeal nerve followed by circumferential placement of local anesthetic. All 5 patients tolerated subsequent awake fiberoptic intubation with either minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
(16 reference statements)
0
18
0
1
Order By: Relevance
“…Blocking the internal branch of the superior laryngeal nerve (iSLN) can achieve the anesthetic effect of the root of tongue, epiglottis, and laryngeal mucosa above glottis fissure [6]. Several studies have also shown that the blockade of the internal branch of the superior laryngeal nerve can be used during fiberoptic bronchoscopy, laryngoscopic surgery, conscious intubation of difficult airway to reduce the hemodynamic change caused by airway stimulation and provide better practical condition for operation [7][8][9]. Although others have reported bilateral iSLN block may reduce the severity of POST in assisted laryngoscopic surgery, we are not aware of any high quality randomized, controlled trials that have investigated the effectiveness of ultrasound guided internal branch of superior laryngeal nerve block (USG-guided iSLN block) on pcostoperative sore throat as compared with atomization inhalation, as treatment for POST.…”
Section: Introductionmentioning
confidence: 99%
“…Blocking the internal branch of the superior laryngeal nerve (iSLN) can achieve the anesthetic effect of the root of tongue, epiglottis, and laryngeal mucosa above glottis fissure [6]. Several studies have also shown that the blockade of the internal branch of the superior laryngeal nerve can be used during fiberoptic bronchoscopy, laryngoscopic surgery, conscious intubation of difficult airway to reduce the hemodynamic change caused by airway stimulation and provide better practical condition for operation [7][8][9]. Although others have reported bilateral iSLN block may reduce the severity of POST in assisted laryngoscopic surgery, we are not aware of any high quality randomized, controlled trials that have investigated the effectiveness of ultrasound guided internal branch of superior laryngeal nerve block (USG-guided iSLN block) on pcostoperative sore throat as compared with atomization inhalation, as treatment for POST.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hockey stick-shaped transducer for ibSLN block has been reported to provide better space for administration of block without compromising the image. [15]…”
Section: Discussionmentioning
confidence: 99%
“…It is normally easily identified by palpation of the cornu of the hyoid bone, but ultrasonography can help identify the anatomy. 17 The cricotracheal membrane ('cricotracheal ligament') is the interspace between the lower border of the cricoid cartilage and the upper border of the first tracheal ring (Fig. 1).…”
Section: Other Membranes For Airway Management At the Front Of The Neckmentioning
confidence: 99%